PARENTS’ AWARENESS OF ASD AND THEIR ATTITUDE TOWARDS AUTISM DIAGNOSTIC TESTS FOR PRE-SCHOOLER - Dina Alahmadi & Hawra Alhashim, Salma Almulla (Migration Letters, 2024)
Autism Spectrum Disorder (ASD) is a neurodevelopmental condition caused by abnormalities in the brain. It is essential for parents to have a thorough understanding of ASD and a positive mindset toward diagnosis a[1]nd associated tests, in order to provide a successful treatment in the case of a child presenting with ASD symptoms. This study aims to evaluate parents’ awareness and attitudes towards ASD and its diagnostic tests for children between the ages of 2 and 6 years old, as well as their possible association with demographic variables. Therefore, a cross-sectional study was conducted between January and February of 2023. Data were collected from the eastern region of KSA (n=392) through a snowball strategy using an online questionnaire to assess knowledge and attitude. The questionnaire utilized in this study was created by reviewing existing literature. Chi-square and logistic regression analysis were conducted using SPSS, and the results revealed a moderate level of knowledge and a neutral attitude, with lower education levels and not knowing an autistic child being significant factors that affected the results, which showed a correlation between low knowledge and negative attitude. Considering these findings, it is critical to expand public awareness of autism spectrum disorder (ASD) in Saudi Arabia, particularly among parents, by launching educational campaigns and providing additional resources for families of children with ASD.